2019
DOI: 10.1111/jam.14198
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of dust‐borneMRSAin pig farms using different approaches

Abstract: Aims To obtain knowledge about (i) how to sample airborne methicillin‐resistant Staphylococcus aureus (MRSA) and dust in the pig farm environment including effects of sampler on (a) measured exposure, (b) MRSA survival and (c) spatial and temporal variation in exposure, and (ii) the association between exposure to MRSA, dust and optical density OD. Methods and Results Airborne dust was sampled on five pig farms using five active and one passive samplers. Staphylococcus aureus and MRSA (as a subset of S. aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…In this study, the concentration of airborne fungi was lower than what has been previous found in pig farms in Poland by a factor of 10 [33] and lower than what was found in Korea by a factor of 2 [34]. Additionally, the concentration of airborne dust was noted to be 1.16 ± 0.18 mg dust/m 3 , which was lower than what was found in another Danish pig farm in the winter of 2015 (average of 1.99 mg dust/m 3 ) [35], and considerably lower in what has been found in older studies (e.g., a geometric mean 4.01 ± 1.73 mg dust/m 3 ) [36]. This could be attributed to the fact that the present study was conducted in a newly built pig farm, which has updated ventilation equipment to reduce the amount of airborne dust.…”
Section: Discussioncontrasting
confidence: 65%
“…In this study, the concentration of airborne fungi was lower than what has been previous found in pig farms in Poland by a factor of 10 [33] and lower than what was found in Korea by a factor of 2 [34]. Additionally, the concentration of airborne dust was noted to be 1.16 ± 0.18 mg dust/m 3 , which was lower than what was found in another Danish pig farm in the winter of 2015 (average of 1.99 mg dust/m 3 ) [35], and considerably lower in what has been found in older studies (e.g., a geometric mean 4.01 ± 1.73 mg dust/m 3 ) [36]. This could be attributed to the fact that the present study was conducted in a newly built pig farm, which has updated ventilation equipment to reduce the amount of airborne dust.…”
Section: Discussioncontrasting
confidence: 65%
“…According to the literature (Agersø et al 2013; Madsen et al 2019), the correct option from the variety of methods of air sampling for microbiological analysis requires the huge knowledge and long experience in the field study. Many different factors can influence the result, such as the concentration of airborne microorganisms (closely related with the type of environment), relative humidity (RH), temperature, species composition, and their ability to survive under unfavourable conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Madsen et al (2019) conducted the study which can be a basis for the description of relevant differences in results (understood as the concentration of airborne MRSA) between six methods of sampling of airborne MRSA (five active and one passive) on five pig farms. Identification of bacteria was carried out on selective agar media using the MALDI-TOF MS method.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the experimental setup, where we used a 1mm 2 plastic mesh insect net to construct the cages, had an effect on the observed difference between the two groups for each room. It is also possible that LA-MRSA dust 49 accumulated on the cages or that caged cultivated house flies were able to touch LA-MRSA positive wild free-roaming flies through the mesh, increasing the LA-MRSA prevalence amongst the caged cultivated house flies. It is however unlikely that a significant proportion of the observed LA-MRSA prevalence amongst the caged cultivated flies can be attributed to direct contact with wild free-roaming flies.…”
Section: Percentage Of Totalmentioning
confidence: 99%